Preparation, characterization, and property evaluation of Hericium erinaceus peptide–calcium chelate - Gu, Haofeng; Liang, Lei; Kang, Yongning; Yu, Rongmiao; Wang, Jiahao; Fan, Dan (Frontiers in Nutrition, 2024)
Recently, owing to the good calcium bioavailability, peptide–calcium chelates made of various foods have been emerging. Hericium erinaceus, an edible fungus, is rich in proteins with a high proportion of calcium-binding amino acids. Thus, mushrooms serve as a good source to prepare peptide–calcium chelates. Herein, the conditions for hydrolyzing Hericium erinaceus peptides (HP) with a good calcium-binding rate (CBR) were investigated, followed by the optimization of HP–calcium chelate (HP-Ca) preparation. Furthermore, the structure of the new chelates was characterized along with the evaluation of gastrointestinal stability and calcium absorption. Papain and a hydrolysis time of 2 h were selected for preparing Hericium erinaceus peptides, and the conditions (pH 8.5, temperature 55°C, time 40 min, and mass ratio of peptide/CaCl2 4:1) were optimal to prepare HP-Ca. Under this condition, the chelates contained 6.79 ± 0.13% of calcium. The morphology and energy disperse spectroscopy (EDS) analysis showed that HP-Ca was loose and porous, with an obvious calcium element signal. The ultraviolet–visible (UV) absorption and Fourier transform infrared spectroscopy (FT-IR) analysis indicated that calcium possibly chelates to HP via interaction with free -COO- from acidic amino acids and C = O from amide. HP-Ca displayed good stability against stimulated gastrointestinal digestion. Moreover, HP-Ca significantly improved the calcium absorption by Caco-2 epithelial cells. Thus, HP-Ca is a promising Ca supplement with high calcium bioavailability.